CYKL POLESKI ALEKSANDRA KUPRINA - Bielniak, Nel (Acta Neophilologica, 2015)
This article analyzes Aleksandr Kuprin’s works creating the so-called Polesye cycle. In his Polesye cycle the writer attempted to present thoroughly a specific sense of the Volhynian Polesye identity that fascinated him. His sightseeing and ethnographic hikes around the region resulted in a series of insightful observations concerning the mentality, customs and appearance of the Polesye population and its attitude toward strangers. Additionally, the trips inspired numerous descriptions of nature, saturated with sensory impressions and the employment of painting devices.